Analisis Akuntabilitas dan Transparansi Pengelolaan Dana Zakat Pada Badan Amil Zakat Nasional Studi Kasus Baznas Kota Bukittinggi - Masri, Waldi; Illahi, Ilham (Jurnal Profiet, 2025)
This study discusses the analysis of accountability and transparency in the management of zakat funds at BAZNAS Bukittinggi City. The unavailability of financial reports on social media and financial report information is still categorized as minimal and is only reported through print media so that the public has difficulty accessing financial reports and does not get clear information related to financial reports. reports can only be accessed by BAZNAS employees. The type of research used in this study is qualitative with a descriptive approach. The data used are primary data, namely observation, interviews, documentation and secondary data sourced from journals. Data collection techniques used are interviews, observations and documentation studies. The results of the study show that the National Zakat Agency (BAZNAS) of Bukittinggi City in managing zakat funds is measured based on accountability and transparency indicators. The researcher found that BAZNAS Bukittinggi City is good in accountability and transparency in managing zakat funds and financial reporting carried out through social media and the official website. The problems faced by BAZNAS Bukittinggi City are that auditing of financial reports has not been carried out and social media financial reports have not been listed in detail. Keywords: Accountability Transparency of BAZNAS Zakat Fund Management